Viabilidade técnica e econômica de um sistema de energia elétrica utilizando biogás obtido de resíduos úmidos de frigorífico de bovinos - Silva, Mírian das Mercês Pereira da (Universidade Federal do Tocantins, 2020)
The world population, since the 1960, has increased significantly. Currently, the planet has 7.2 billion inhabitants. With this increase in population, electric power generation, food production, solid waste generation and, consequently, the burning of fossil fuels that are responsible for the emission of so-called greenhouse gases (GEE) and are directly related to the intensification of the greenhouse effect and the occurrence of climate change. The generation and use of biogas is consolidated as an important alternative for the process of environmental sustainability. The significant agricultural and livestock production indicates a significant potential of biogas production from waste from the slaughtered animals, using biogas, instead of fossil fuels. In this context, the present study aimed to estimate the biomass energy production, evaluating the technical and economic feasibility of the system. For technical feasibility, a time series was presented using the Integrated Automatic Regressive of Moving Average (ARIMA) model for monthly forecast of slaughtered animals, production of biomass and electric energy. Economic viability was evaluated through investment analysis indicators: Net Present Value (VPL); Internal Rate of Return (TIR) and Payback Period. The ARIMA linear autoregressive method generated data within the 95% confidence interval. The model was significant, between observation and projection of the series, which was practically constant for the forecast horizon of six months. The values resulting from the analysis of the economic viability were favorable, presenting discounted payback of 8.11 years, TMA of 5% and TIR of 9.78%. The study demonstrated that there is a technical and economical feasibility in the implementation of a biodigestion system using humid residues from cattle refrigerators, making possible to improve the use of this important source of renewable energy.